2021
DOI: 10.1111/jcmm.16969
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pyroptosis‐related lncRNAs for constructing a prognostic model and their correlation with immune infiltration in breast cancer

Abstract: Breast cancer (BC) is the most frequently diagnosed female malignancy and one of the leading causes of cancer-related mortality among women worldwide. 1 BC is a highly complex cancer type with histological and molecular heterogeneity, posing an enormous threat to women health due to its extremely high recurrence rate and mortality rate. 2 Although the therapeutic efficacy of BC gains momentum dramatically, unfortunately, the lack of effective hallmarks and diagnostic tools to predict prognosis or long-term sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Hydrogen inhibits endometrial cancer progression by activating the CASP1/GSDMD-mediated pyroptosis pathway ( Yang et al, 2020 ). To date, some studies have explored the roles of pyroptosis regulatory genes (PRGs) in endometrial cancer ( Zhang and Yang 2021 ), ovarian cancer ( Ye et al, 2021 ), and breast cancer ( Lv et al, 2021 ). These findings undoubtedly point toward the fact that pyroptosis profoundly affects the prognosis and immune process in multiple cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen inhibits endometrial cancer progression by activating the CASP1/GSDMD-mediated pyroptosis pathway ( Yang et al, 2020 ). To date, some studies have explored the roles of pyroptosis regulatory genes (PRGs) in endometrial cancer ( Zhang and Yang 2021 ), ovarian cancer ( Ye et al, 2021 ), and breast cancer ( Lv et al, 2021 ). These findings undoubtedly point toward the fact that pyroptosis profoundly affects the prognosis and immune process in multiple cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it has been proved that lncRNAs engage in cancer‐related cellular pathways and have good predictive power in prognosis and diagnosis 22,23 . Emerging studies have tried to establish novel and effective lncRNAs pattern risk models in malignancy, 24,25 as well as discover molecular character and potential therapy targets of breast cancer patients 26,27 . Until now, the patterns of necroptosis‐related lncRNAs in BC and the potential capability of predicting the prognosis has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have shown that the occurrence of tumor is closely related to the pyroptosis, which has a certain inhibitory effect on the emergence and growth of tumors in a variety of cancers, such as lung cancer, leukemia, melanoma and other tumors [16][17][18][19][20][21][22][23][24][25][26][27] . pyroptosis has a certain expression in the genes of BC patients, and the relevant literature has introduced and information mining [11][12][13][28][29][30] . In the study of BC, the over expression of GSDMB is related with poorer prognosis and tumorous progression [31] .…”
Section: Discussionmentioning
confidence: 99%
“…The ROC curve analysis of GEO and TCGA cohorts demonstrates that our prognostic model has good performance (Figure 5K-L). Furthermore, ROC data were collected from other literatures [11][12][13] on BC prognostic model of final significant prognosis-related genes. After extracting the same data set GSE42568, a horizontal comparison was made.…”
Section: Evaluation and Analysis Of The Risk Modelmentioning
confidence: 99%